Assessment of water use efficiency of fruit trees for sustainability in the El Ghanima irrigated farm (Medjerda river basin, North Tunisia) - Ahmed Skhiri; Tasnim Hajji; Salem Mabrouk; Slaheddine Khlifi (African Journal of Advanced Pure and Applied Sciences, 2025)
The El Ghanima Farm is located at Sidi Brahim district, as the closest irrigated area downstream of Sidi Salem dam. The climate is semiarid with annual precipitation around 450 mm yr-1. The irrigated cropping system is diversified including vegetable crops, fruit trees, and field crops; this study focuses on fruit trees. The El Ghanima society manages the largest agricultural farm in the district, with an area of 320 ha. The water source needs are provided by pumping from wadi Medjerda through Sidi Salem release and groundwater during water shortage. This study aims to identify the exploitation plan for optimal economic profitability (DT m-3) in the irrigated farm of El Ghanima. This plan takes into account the irrigation water availability, its quality, and the pedoclimatic characteristics of the study area. The approach involves accounting for expenses and revenues, as well as calculating irrigation water consumption to assess the water economic profitability. The goal is to identify the crop that maximizes the irrigation water value and tolerates technical, water, and pedoclimatic constraints. Results indicate that the water profitability is influenced by crop water requirements and tolerance to salinity, water cost, and price market. Considering cropping system of the farm, almond and citrus trees are currently the most profitable crops in terms of water use efficiency. However, these crops are sensitive to salinity and may become less profitable in the future. Olive trees and pomegranates are more tolerant to salinity and may become more attractive options in the long term. Water-saving techniques and improved water management practices are essential for sustainable irrigation. Overall, this study provides valuable insights into the complex relationship between water availability, crop selection, and profitability in the context of water scarcity. The findings can be used to guide future agricultural development in Sidi Brahim district and other water-scarce regions.